THE IMPACT OF UNREGISTERED (SIRI) MARRIAGE IN THE PERSPECTIVE OF INDONESIAN MARRIAGE LAW: A CASE STUDY IN RACEK VILLAGE, TIRIS DISTRICT, PROBOLINGGO REGENCY - Imam Mustofa (International Journal of Multidisciplinary Reseach, 2025)
The phenomenon of underage unregistered (siri) marriages remains prevalent in various rural areas of Indonesia, including Racek Village, Tiris District, Probolinggo Regency. This practice is often carried out without official state registration and involves couples who have not yet reached the legal age of adulthood. This study aims to analyze the causes of underage unregistered marriages, examine their impact on household harmony, and review the practice from the perspectives of Indonesian marriage law and Islamic law. The research employs a juridical-empirical and sociological approach, collecting data through interviews and observations involving underage married couples, community leaders, and village officials.The findings reveal that economic hardship, low educational attainment, and the persistence of local cultural traditions are the primary factors driving underage unregistered marriages. The impacts include emotional instability, economic pressure, domestic conflict, and the deprivation of legal rights for both spouses and children. From the perspective of positive law, this practice contradicts Law No. 16 of 2019 on Marriage and the principles of child protection. From the standpoint of Islamic law, it is inconsistent with the objectives of maqāṣid al-syarī‘ah, particularly the principle of hifz al-nasl (protection of lineage).This study recommends strengthening the roles of government institutions, religious authorities, and local communities in legal education and family guidance programs to prevent child marriage.